2015
DOI: 10.3945/ajcn.115.115402
|View full text |Cite
|
Sign up to set email alerts
|

Short-term variability in body weight predicts long-term weight gain

Abstract: Elevated weight variability in young women may signal the degradation of body weight regulatory systems. In an obesogenic environment this may eventuate in accelerated weight gain, particularly in those with a genetic susceptibility toward overweight. Future research is needed to evaluate the reliability of weight variability as a predictor of future weight gain and the sources of its predictive effect. The trial on which this study is based is registered at clinicaltrials.gov as NCT00456131.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(47 citation statements)
references
References 29 publications
1
45
0
1
Order By: Relevance
“…These predictors, especially the higher baseline BMI, have been previously noted (11,12). Lowe et al (31,32) found that weight variability over a 6-month period predicted weight gain over 2 years in college females. Weight suppression has also been predictive of weight gain.…”
Section: Clinical Trials and Investigationsmentioning
confidence: 64%
“…These predictors, especially the higher baseline BMI, have been previously noted (11,12). Lowe et al (31,32) found that weight variability over a 6-month period predicted weight gain over 2 years in college females. Weight suppression has also been predictive of weight gain.…”
Section: Clinical Trials and Investigationsmentioning
confidence: 64%
“…First, increased weight variability might represent some sort of early marker that is ultimately associated with a chronic positive energy balance and weight gain (1). The magnitude of the neural response that predicts weight variability in the current study reflects the potential utility of weight variability in addition to weight gain in the understanding of eating and weight regulation.…”
Section: Figurementioning
confidence: 82%
“…Because of missing weights at the 3-y follow-up, 127 total participants were analyzed in the supplementary analysis with the BMI change controlled for. BMI variability was selected as the outcome of interest in analyses because all of the extant literature on weight variability has used either BMI or raw weights (16,17). However, some studies that used the same or similar paradigms used body fat as the outcome of interest (18).…”
Section: Fmri Paradigmmentioning
confidence: 99%
See 2 more Smart Citations